Hypertension, Asymmetric Renal Parenchymal Defect, Sterile Urine, and High E. coli Antibody Titre. Issue 5870 (7th July 1973) - Andersen, H. J.; Jacobsson, B.; Larsson, H.; Winberg, J.
Abstract : During an 11-year period four children were seen with asymmetric renal parenchymal reduction, arterial hypertension, and sterile urine. The history and radio-logical or histological findings, or both, were consistent with "abacterial pyelonephritis" induced by bacterial infection in early childhood. All four had raised antibody titres to Escherichia coli. Three possibilities may explain the high antibody titres and insidious course of the renal damage—the presence of bacterial variants or amorphous bacterial antigen in the kidneys or the fact that because of cross-reactivity between certain E. coli O antigens and renal tissue the "E. coli antibodies" were, in fact, autoantibodies.